Square peg round hole: navigating operational and interdisciplinary challenges in a co-produced, community-based research partnership - Emma Tuschick; Jo Smith; Matthew Cotton; Jibin He; Ashley Blacklock; Cara Jordan; Helen J Moore; Amelia A Lake; Lisa Harris; Lesley Lowe; Kim Baines; Joe Dunne; et al. (Research Involvement and Engagement)
Abstract Background Inclusive, community-based research is increasingly important for aligning academic work with real-world needs. This paper describes the challenges and successes of a research collaboration between academic, health service, and voluntary sector partners, working together to address nutrition and food waste for individuals with severe mental illness. Methods This reflective article reports a primary study evaluation of the process of a co-produced project aimed at developing a nutritious ready meal from surplus food to be distributed through Eco Shops, involving individuals with severe mental illness (SMI). A collaborative partnership was formed between a University, an NHS Foundation Trust, and a Voluntary Sector Organisation in the North-East of England. Data for this process evaluation were collected through a team questionnaire evaluating all aspects of the collaboration, including ethics, governance, and communication practices. Results While the overall project achieved positive outcomes, the collaborative research process included substantial challenges in ethical and governance alignment, collaborative working practices, and communication across diverse organisational cultures. Conclusion This study highlights the need for flexible governance, clear communication protocols, and effective workload management in cross-sector collaborations. Insights emphasise adapting project frameworks to support interdisciplinary, community-focused research for successful, sustainable partnerships.